A unique approach to fostering student wellbeing while supporting community needs through an interprofessional, One Health, access to care veterinary clinic: WisCARES - Alvarez, Elizabeth E.; Chun, Ruthanne; Brooks, Jennifer W.; Schultz, Kelly; Lygo-Baker, Simon (Frontiers in Veterinary Science, 2025)
Service-learning, defined as integrating student education into academically relevant service activities to address a community need, is a way for students to learn and practice multiple skills. WisCARES (Wisconsin Companion Animal Resources, Education and Social Services) is a service-learning clinic in which veterinarians, veterinary nurses, and social workers form an interprofessional team providing a unique educational opportunity within a One Health access-to-care clinic with care for both the veterinary patient and the client. In addition to hands-on experiences in spectrum of care medicine, veterinary students learn about poverty, homelessness, and social determinants of health, and how these impact clients’ decision making and ability to adhere to treatment recommendations. They also work with social workers to understand how moral stress and perfectionism can impact their physical and mental health and develop a self-care plan to address their own stressors. WisCARES’ goal is to help students develop into veterinarians who will be positive additions the profession by recognizing and challenging their own biases, and by consciously integrating access-to-care medicine into their future practice for the wellbeing of their veterinary team and the community they serve.